Implementation and impact of the global access principles at the University of British Columbia: current successes and future challenges - Gallini, Nancy; Hancock, Robert E. W.; Lester, Richard; Sharp, Brett; Wasan, Kishor M. (Frontiers in Pharmacology, 2023)
In 2007, the University of British Columbia (UBC) was the first university in Canada, in collaboration with the UBC chapter of Universities Allied for Essential Medicines, to develop and adopt a set of global access (GA) principles and strategies for research, licensing and patenting of new innovations, aimed at providing affordable access to technologies developed from UBC research throughout the developing world and among vulnerable populations. In this perspective brief note, we provide an update of UBC's progress made on several technologies that fall under the GA principles over the past 15 years., since the initial phase of UBC's global access initiative was reported in this journal in 2009. Technologies are wide-ranging, including an oral medication for the treatment of leishmaniasis in India; peptides for potential global use against malaria, and various bacterial, viral and fungal infections; ainfections; a portable vaccine cooler for developing countries; a diagnostic technology to detect severe sepsis; and an SMS Messaging System to monitor and support patients with HIV, TB and COVID-19 in Africa. We identify challenges faced by the researchers in implementing the GA principles for these technologies and potential solutions for overcoming them through creative licensing and partnerships with public and private sectors, governments, local companiescompanies, and communities. As the UBC example illustrates, universities across the globe have an opportunity to make a social impact on improving global health of vulnerable populations and support a local infrastructure that can sustain these improvements.